Analyzing industry changes and business evolution: the path forward for Midwest Equipment Company. Issue 1 (30th March 2019) - Straub, Larry Gene; Perry, John
Abstract : Theoretical basis: The case illustrates how environmental forces affect an industry's profitability. PESTEL and five forces analyses can be used to examine the retail agricultural equipment industry. Research methodology: Single case study. Case overview/synopsis: Jonathan Sullivan has a decision to make. His company is struggling due to difficult industry conditions. He is questioning if the company can continue to survive. MEC is an agricultural equipment dealer. The industry has experienced boom-and-bust periods since the company was founded. But the current downturn seems different. The past five years have been difficult as manufacturers have changed their dealership practices. Jonathan has struggled with some of the new practices the manufacturers have implemented. These new practices could negatively impact the company's ability to survive. Jonathan wonders, "What is the best path forward for the business?" Complexity academic level: The case is designed to be used in an undergraduate strategic management course.